How Do Parents Support the Autonomy of Toddlers? - Coza, Maria-Madalina (Technium Social Sciences Journal, 2025)
The purpose of this article is to explore how the parents of toddlers attending day care define, understand, and support children’s autonomy within the family environment. The research is framed within the constructivist–interpretive paradigm, in which reality is conceived as plural, socially constructed, and context-dependent. From this perspective, toddler autonomy is understood not as an objective and universal given, but as a phenomenon that manifests and acquires meaning differently according to interactions, cultural contexts, and parental representations. A qualitative, ethnographic design was chosen, as it allows for an in-depth understanding of parental practices and the meanings they attribute to the phenomenon under investigation. A total of 92 parents, representing 46 families (46 mothers and 46 fathers) of toddlers attending two day care centers in Bucharest, participated in three photovoice workshops conducted in June 2024. The findings indicate that parents do not conceptualize toddler autonomy as a singular ability, but rather as a complex and multidimensional process constructed within everyday and relational contexts. The analysis of the identified dimensions—practical and functional autonomy, emotional, cognitive, and relational autonomy, participation in family life, environmental exploration, and risk-taking—confirms the specialized literature regarding the progressive and interactional nature of early autonomy.